Analysis of the Suitability of Infant Food Composition in “Babyfood X” in Compliance with Halal Certification Regulations: Analisis Kesesuaian Komposisi Makanan Bayi di “Babyfood X” terhadap Kepatuhan Regulasi Sertifikasi Halal - Rafdiansyah, Muhammad Ainur; Nurbaya, Syarifa Ramadhani; Handayani, Puspita; Azara, Rima (Universitas Muhammadiyah Sidoarjo, 2025)
This article aims to analyze the suitability of the composition of baby food produced by